- #1

- 12

- 0

[tex]\lim_{n \rightarrow a} f(g(x)) = f(\lim_{n \rightarrow a} g(x))[/tex]

for monotonic [tex]f[/tex], some [tex]a[/tex], and such that if the limit does not exist for one side of the expression, it doesn't exist for both?

Thanks.

You are using an out of date browser. It may not display this or other websites correctly.

You should upgrade or use an alternative browser.

You should upgrade or use an alternative browser.

- Thread starter tunaaa
- Start date

- #1

- 12

- 0

[tex]\lim_{n \rightarrow a} f(g(x)) = f(\lim_{n \rightarrow a} g(x))[/tex]

for monotonic [tex]f[/tex], some [tex]a[/tex], and such that if the limit does not exist for one side of the expression, it doesn't exist for both?

Thanks.

- #2

mathman

Science Advisor

- 7,924

- 467

Your original equation does not describe the dependence on n of anything.

- #3

- 12

- 0

Sorry, replace n with x - was very tired!

- #4

- 12

- 0

Correction: [tex]\lim_{x \rightarrow a} f(g(x)) = f(\lim_{x \rightarrow a} g(x))[/tex]

- #5

mathman

Science Advisor

- 7,924

- 467

Share: